Isolation and characterization of microsatellite markers for the banded ironstone endemic acacia karina (Leguminosae: Mimosaceae) and cross-species amplification with A. stanleyi and A. jibberdingensis - Nevill, Paul; Anthony, J.; Krauss, S. (Springer, 2010)
Microsatellite markers were developed for the banded ironstone endemic shrub Acacia karina to examine genetic diversity, range-wide differentiation and mating system parameters. Nine loci were developed and in a sample of 20 individuals from one population the number of alleles ranged from 4 to 12 per locus and observed heterozygosities from 0.556 to 0.824. All loci were tested for cross-species amplification in two other south-west Australian Acacia species thought to be closely related to A. karina. Of these nine loci, eight were polymorphic in A. jibberdingensis and three in A. stanleyi. © Springer Science+Business Media B.V. 2010.